An intertextual and interdiscursive analysis of contemporary thinking about womanhood in Mokitimi's (1997) the voice of the people: proverbs of the Basotho - Manyawu, Andrew T. (National Inquiry Services Centre, 2016)
Discourses evolve over time in line with the dynamic nature of culture and so do the identities and power relations that they build. The change reflected in discourse points to the nature and extent of the changes taking place in society. To document such discursive changes is therefore to keep a record of patterns of the socio-cultural evolution impacting values, norms and attitudes. By collocating Sotho traditional wisdom in the form of proverbs with the English explanation of the same, Mokitimi (1997) offers a compelling illustration of what such a shift in meaning might look like. This article argues that Mokitimi's (1997) treatment of proverbs exploits intertextual and interdiscursive spaces (Kristeva, 1980; Fairclough, 1992; Bhatia, 2010) for the critical evaluation and semantic adjustment of gender-based identities and power relations in the light of contemporary thinking. It shows how two discourse configurations (that of the proverb and that of its explanation) reflect two often conflicting perceptions of womanhood, each aligned to a different worldview marked by a different era in Sotho socio-cultural development. Thus an explanation text critically evaluates the adequacy of a proverb's traditional wisdom in the light of contemporary thinking and adjusts its meaning accordingly where necessar